Contrasting the crospovidones functionality as excipients for direct compression - Daniel García Ramírez; Leopoldo Villafuerte Robles (Universidade de São Paulo, 2015)
Specific values of technological properties of excipients allow the establishment of numerical parameters to define and compare their functionality. This study investigates the functionality of Polyplasdones XL and XL10. Parameters studied included tablet disintegration profiles, compactibility profiles and powder flow. The results allowed the establishment of quantitative surrogate functionalities of technological performance, such as absolute number, and as a value relative to the known microcrystalline cellulose type 102. Moreover, the establishment of an explicit functionality to improve the technological performance of two diluents and a model drug was investigated, as was setting up of these functionalities, as quantitative values, to determine the input variables of each material and its probable functionality in a drug product. Disintegration times of pure Polyplasdone XL and its admixtures were around half that of Polyplasdone XL10. The improvement in tablet compactibility was 25-50% greater for Polyplasdone XL10 than Polyplasdone XL. Crospovidones proportions of up to 10% have little effect on the flow properties of other powders, although pure Polyplasdone XL10 and its admixtures display compressibility indexes about 20% greater than Polyplasdone XL. The observed results are in line with a smaller particle size of Polyplasdone XL10 compared to Polyplasdone XL.